DEVELOPMENT AND EVALUATION OF ADVANCED WELDING TECHNIQUES FOR JOINING DISSIMILAR METALLIC MATERIALS - Salokhiddin , Azimov; Toshqobilov , Javohir (Techscience uz - Topical Issues of Technical Sciences, 2025)
This study focuses on welding dissimilar metals, specifically ferritic alloy-steel and nickel alloys, using GTAW and SMAW with ERNiCr-3 filler. Due to differing material properties, joining is challenging. Mechanical tests showed that GTAW with ERNiCr-3 ensures high joint strength and corrosion resistance, enhancing reliability in critical industries.